POST-TRAUMATIC CSF LEAK IN PATIENTS PRESENTING WITH PNEUMOCEPHALUS - MATEEN, U; SAEED, S; SHAH, IA; KHULSAI, MS; ALI, F; TALREJA, V; KHAN, AA (Biological and Clinical Sciences Research Journal, 2024)
Post-traumatic cerebrospinal fluid (CSF) leak is a serious complication associated with skull base fractures and pneumocephalus, often resulting from traumatic brain injuries. Understanding the frequency and timely management of these leaks is crucial to preventing further complications and improving patient outcomes. Objective: The objective of this study was to determine the frequency of post-traumatic CSF leak in patients with skull base fractures presenting with pneumocephalus. Methods: After ethical approval from the institutional review board, this prospective cross-sectional study was conducted at the Emergency Department of Shaheed Mohtarma Benazir Bhutto Trauma Centre (SMBBTC), Karachi, from December 2022 to December 2023. Seventy-three patients with skull base fractures were recruited. Each patient underwent comprehensive evaluation, including medical history, clinical examination, and radiological assessment using CT and MRI scans to confirm brain injury. A follow-up CT scan was performed 24 hours post-admission to assess for pneumocephalus and other intracranial injuries. Subsequent CT scans were conducted at 3 and 5 days for stable patients with moderate to severe head trauma. Data were analyzed using descriptive statistics. Results: Among the 73 patients, the majority were males (75%) and aged 16-30 years (27%). Ear bleeding was observed in 30% of patients, nose bleeding in 56%, and raccoon eyes in 42%. CSF leakage was detected in 10 patients (14%), with 60% of these cases presenting as rhinorrhea. Road traffic accidents accounted for 70% of the cases. Pneumocephalus was detected in 71% of patients within the first 24 hours. Air over the convexity was observed in 55% of patients on CT scans. CSF leak occurred within 24 hours in 50% of the patients and resolved in 40% within two weeks. Repeat CT scans showed improvement of pneumocephalus in 68% of patients. Conclusion: Timely detection of pneumocephalus and prompt surgical intervention can effectively reduce adverse health effects and prevent potential complications in patients with skull base fractures.